A case of feline gastrointestinal eosinophilic sclerosing fibroplasia limited to the mesentery. (30th April 2018) - Kambe, N.; Okabe, R.; Osada, H.; Ogawa, M.; Kishimoto, M.; Fukushima, R.; Kondo, H.; Ohmori, K.
Abstract : An entire, female, mixed‐breed cat of unknown age was presented with a 6‐week history of lethargy, anorexia and vomiting. There was an increase in the number of white blood cells in the blood, including neutrophils and eosinophils; moderate anaemia; ascites; and possible mesenteric peritonitis. Exploratory laparotomy revealed firm, multifocal small nodules in the mesentery. As the nodules were surgically unresectable, they were biopsied. Histologically, the nodules were composed of thin trabeculae of dense collagen fibres mixed with plump fibroblasts and numerous eosinophils, consistent with feline gastrointestinal eosinophilic sclerosing fibroplasia. Bacteria were not detected on histological examination of the nodules and cytology of the ascites. Remission of disease occurred following treatment with prednisolone and ciclosporin A for 22 days and antibiotics for 40 days. After remission, ciclosporin A was administered for 236 days and then discontinued. Eosinophilia also resolved after treatment with ciclosporin A. The cat is still alive and in good condition on day 689. This report describes what may be an atypical case of feline gastrointestinal eosinophilic sclerosing fibroplasia, lacking involvement of the gastrointestinal tract, and was apparently cured by treatment that involved ciclosporin A.